(3GdQhVI GdajMGA aj JGQjN GdfSGAs - (3jGSjf Hf NjQGddg Hf eMehO Hf ehSi GdNWjH GdYeQj,J (B1232 (3g` s
(3ChdgG (B:s
(3CeG HYO efP fTCJ de CRd CWGdY cJH GdJhGQjN GdeJbOeI Ke CLHJ Cf CLeY cJGHkG ai JGQjN GdfSGA GdUGdMGJ , hfHPI ai HYV GdfSGA GdWGdMGJ s
(3BNQgG (B:s
(3adeG cGfJ GddjdI GdJi YjfgG GdefLehf (B,(3de JgH QjM , hdG QCjfG djdI eKdgG ai QchOgG s
(3Vef eLehY , JQJjHgG (B: (3Chd TF ajgGs
(3Jhai GdeDda HYO SfI (B1232(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B129 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B177s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B215 s
Keywords: (3GdJGQjNs